PERTUMBUHAN TANAMAN PAKCOY (Brassica chinensis L.) DENGAN PEMBERIAN TRICHOKOMPOS KOTORAN AYAM PADA TANAH GAMBUT - Mukarlina, Mukarlina; Turnip, Masnur; Bahari, Anggi Dwi (BUANA SAINS, 2024)
This research aimed to determine the addition of chicken manure trichocompost to increase the growth of pakcoy. This study used a completely randomized design with 5 levels of trichocompost fertilizer treatment, namely without trichocompost fertilizer (Control), 40 grams, 60 grams, 80 grams, and 100 grams. The results showed that the application of chicken manure trichocompost 100 grams was the treatment that gave the best results on the growth of pakcoy plants for the parameters of the average number of leaves (15.6 leaves), leaf area (41.04 cm2), crown wet weight (52.64 grams) and roots (2, 52 grams), dry weight of shoots (2.00 grams) and roots (0.25 grams), and leaf coarse fiber content (1.51%).